Audiovisual services in Korea: Market development and policies - Yeongkwan Song (Asian Development Bank Institute (ADBI), 2012)
This paper reviews economic development and the regulatory environment of audiovisual services in the Republic of Korea (hereafter, Korea). The paper specifically examines motion pictures and broadcasting, and discusses what drives or hinders the sector's trade potential. Korean motion pictures have benefited greatly from the elimination of government censorship, substantial investment capital, especially from the 1990s, and frequent invitations from prestigious international movie festivals. The trade potential of Korean audiovisual services depends on whether Korean audiovisual services providers create high quality content that can be shared locally and/or universally. As recently proven in Korea's film industry, Korean content does have trade potential. The most important prerequisite for high quality content is the generation of creative ideas, which would be hindered by strong government censorship and controls. The restrictive Korean broadcasting sector should learn from the success of the Korean film industry in this regard.
Keywords: O14; O24; O53; 330; audiovisual services; republic of korea; motion pictures; broadcasting; Multimedia; Fernsehprogramm; Film; Handelsliberalisierung; Dienstleistungshandel; Kulturpolitik; Südkorea